Quantifying cycles of tectonically induced vertical surface motions in an accretionary wedge: evidence from foraminiferal-based Plio-Pleistocene paleo-water depth estimates of the Island of Rhodes (Greece) - Eichner, Daniela; Schmiedl, Gerhard; Titschack, Jürgen; Riller, Ulrich; Andersen, Nils; Ferreira, Malu; Milker, Yvonne (Quaternary science reviews, 2025)
The Island of Rhodes, located in the Eastern Mediterranean Sea at the eastern terminus of the Hellenic forearc, experienced intensive tectonic motions during the Plio-Pleistocene. Marine sediments of the Lindos Bay Formation, Plio-Pleistocene in age, were uplifted and are outcropping today along the eastern coast of the island. These sediments offer an unique opportunity to unravel the complex depositional and neotectonic history of Rhodes. In this study, we provide new paleo-water depth data from the Cape Vagia sediment section and summarize and integrate these results with existing data of paleo-water depth changes during the deposition of the Lindos Bay Formation. Paleo-water depth reconstructions were obtained by using an existing transfer function, applied to the fossil benthic foraminiferal assemblages. In doing so, the full cycle of subsidence and surface uplift of the eastern coast of the Island of Rhodes during the Plio-Pleistocene was reconstructed for the first time. Accordingly, our data indicates a maximum surface uplift of ∼700 m since the Early Pleistocene. Each of the presented sediment sections further revealed distinct short-term tectonically controlled surface uplifts with rates up to 10 mm a−1. Such rates occur regularly throughout the Plio-Pleistocene sedimentary records on Rhodes and do not seem to be related to the long-term uplift or subsidence trend of the island. Furthermore, the sedimentary records reveal differences in the timing and amplitudes of vertical motions among individual depocenters. These differences can be explained by an interplay between island-wide and local vertical surface motions, of which the latter may be due to the activity of kilometer-scale normal faults. Accretionary wedge dynamics can account for the observed temporal and spatial variations in vertical surface motions on the eastern coast of Rhodes.